Factors Causing Maternal Death due to COVID-19 in Several Countries: A Literature Review - Mustofa, Vina Firmanty; Prasetyo, Budi; Indriani, Diah; Rahmawati, Nur Anisah (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Since 2019, the world has been faced with a global crisis. The spread of SARS-CoV-2 has an impact on all populations, including pregnant women, who are among the most vulnerable and at-risk population groups. The worldwide spread of the virus is called the COVID-19 pandemic. This study aims to explore the factors that cause maternal death during pregnancy and postpartum due to COVID-19 in several countries.Method: A literature review was conducted to explore broadly the causes of maternal deaths due to COVID in several countries. Article search on three databases, namely PubMed, Google Scholar, and ScienceDirect. A total of 7 articles were analyzed. The data studied are cases of death and their causes.Results: The study was conducted in the period 2018 to 2021 with the type of research using retrospective data. When compared to before the pandemic, there was a significant increase in the number of maternal deaths. Factors that increase the risk of maternal death come from direct and indirect factors. Indirect factors such as age, health facility access, inadequate tools, and health services, access to knowledge, cultural practice, and poverty. Direct factors are comorbidities such as obesity, diabetes, cardiovascular disease, hypertension, and immune impairment. Pregnant women who do not have comorbidities can have a poor prognosis with undetected causes of death. Health facilities need to conduct early screening so that direct and indirect factors can be minimized to prevent maternal mortality.